2015
DOI: 10.1039/c4an00815d
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and identification of a series of alkyl decalin isomers in petroleum geological samples

Abstract: The comprehensive two-dimensional gas chromatography/time-of-flight mass spectrometry (GC × GC/TOFMS) has been used to characterize a crude oil and a source rock extract sample. During the process, a series of pairwise components between monocyclic alkanes and mono-aromatics have been discovered. After tentative assignments of decahydronaphthalene isomers, a series of alkyl decalin isomers have been synthesized and used for identification and validation of these petroleum compounds. From both the MS and chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
(39 reference statements)
1
3
0
Order By: Relevance
“…Up to 11% of the observed mass fraction of diesel fuel has also been attributed to bicyclic alkanes . In this study, we identify alkyl-decalins without the use of authentic standards owing to the characteristic mass spectra obtained for these compounds, with the presence of their corresponding molecular ion; the mass fragments of the respective observed isomers are in good agreement with the results published by Wang et al Alkyl-decalins were identified by their characteristic mass fragment m / z 137 together with the molecular ion (using 14 eV spectra). The two closely eluting peaks correspond to the alkyl chain at the 1- and 2- positions of the decahydronaphthalene structure but cannot be distinguished from one another.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Up to 11% of the observed mass fraction of diesel fuel has also been attributed to bicyclic alkanes . In this study, we identify alkyl-decalins without the use of authentic standards owing to the characteristic mass spectra obtained for these compounds, with the presence of their corresponding molecular ion; the mass fragments of the respective observed isomers are in good agreement with the results published by Wang et al Alkyl-decalins were identified by their characteristic mass fragment m / z 137 together with the molecular ion (using 14 eV spectra). The two closely eluting peaks correspond to the alkyl chain at the 1- and 2- positions of the decahydronaphthalene structure but cannot be distinguished from one another.…”
Section: Resultssupporting
confidence: 89%
“…Avila et al utilized GC×GC-ToF-MS and EI coupled to Fourier transform cyclotron resonance mass spectrometry to analyze compounds found in heavy gas oils, tentatively identifying alkyl-decalins. More recently, however, Wang et al characterized these compounds by synthesizing and investigating their mass spectra using GC×GC-ToF-MS, reporting the mass spectra and retention times for decalins ranging from C 1 to C 11 in alkyl chain length. Worton et al reported that bicyclic alkanes with various branched alkyl chains contributed about 30% of the observed mass in POA and lubricating oil.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, drilling fluids might be contaminated by the geogenic organic compounds due to their recycling process. For instance, 1,2,3,4-tetrahydronaphthalene, and naphthalene, decahydro-2-methyl- might be the natural PMT/vPvM substances from shale formation. , This suggests that the natural PMT/vPvM substances are also worth attention, besides the artificial PMT/vPvM substances. The detailed information on sources for these PMT/vPvM substances is presented in Supporting Information (Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al, 462 2015 Identification and validation of decahydronaphthalene isomers in crude oil and a source rock extract sample Zhang et al, 463 2015…”
Section: Advances In Analytical Tools For Complexmentioning
confidence: 99%